Adenocarcinoma of Meibomian glands in Male- A rare case report (Community Based Medical Journal, 2013)
A 50 years old male presented with recurrent multinodular growth on the right upper eyelid mimicking multiple chalazion for the last two years. He was treated as chalazion two times but recurred. A full thickness wide excisional biopsy of the lesion along with normal lid tissue done. Histopathological report was Adenocarcinoma of the meibomian gland of the right upper lid. Lid reconstruction done by lid sharing procedure. Result of the treatment was excellent after follow up period of six months with good lid function and no significant complication. DOI: http://dx.doi.org/10.3329/cbmj.v2i1.14189 Community Based Medical Journal Vol.2(1) 2013 69-72